향토자원 산업화를 위한 문화콘텐츠 개발 요소 : 광양 홍쌍리청매실농원의 문화콘텐츠 요소 분석 - 윤유석 (한국농촌경제연구원, 2010)
This paper analyzes the development elements of rural cultural contents that have contributed to the success of Hong Ssang Ri's Cheong Maesil Plum Farm in Gwangyang. At the farm, cultural events have been held in the form of festivals, tours, experience programs and exhibitions. Specifically, Hong Ssang Ri, who is the founder of the farm and a master of traditional food using plums as a main ingredient, tells her stories of how she developed the maesil plum into a traditional local resource through a book, a photo album, exhibits, description boards and others. The analysis methods used in this study are the narrative theory of narrative structure (express substance, express form, content substance, content form) and narrating elements (addresser, addressee, narrative, and narrating method). Hong Ssang Ri has narrated her stories to mothers, farmers, and unhealthy individuals to share her experiences, knowledge, feelings and thoughts. These narrative contents make people to understand the plum's value and meaning. In the process of industrializing the plum, the cultural contents of stories to share with consumers have contributed to the promotion of the plum by storytelling the brand ‘Hong Ssang Ri’ and the region ‘Gwangyang’.
Keywords: 향토자원; 산업화; 문화콘텐츠; 홍쌍리; traditional local resources; industrialization; cultural-contents; Hong Ssang Ri